SOLAR DISTILLER IN A PYRAMIDAL COVERING AND ISOLATION WITH COMPOSITE MATERIAL - Cöuras Ford, E. T. L.; Ribeiro, F. A.; Lima, R. V.; Souza, E. M. (Revista de Engenharia Térmica, 2008)
To demonstrate the thermal calorific and economic viability of the material, compared to the others conventional distiller, here is presented a solar distiller of simple stage, witch has as main differential characteristics the geometry of the covering and the material used to make its coating. The model built has an area of 0.25 m² and pyramidal covering, witch allows the collection of the distillate water in the four faces, different of just two like is found in the conventional distiller, besides promote the absorption of the radiation because of its versatility about the positioning of the sun. Not despite, its built is favored for the low cost associated and the agility in the process because it is made with a mix of gypsum, EPS ground and water, witch also attributes to the distiller thermal properties more favorable to the process of distillation.